Histórias Sociais e crianças com autismo: mapeamento da literatura e proposta de treinamento online de mães - Lazzarini, Fernanda Squassoni (2022)
Individuals with Autism Spectrum Disorder (ASD) may have deficits in social interactions that can lead to inappropriate behaviors. Some authors have been successful in using social stories to promote social performance and decrease inappropriate behavior. Social Stories™ are short, self-paced stories that can be used to help people with ASD interpret and understand difficult, confusing, or new social situations. These stories are used to describe social situations in which an individual may have difficulty identifying relevant social cues or expected behaviors, as well as serving to understand the consequences of behaving in different ways. This thesis was divided into two studies. Study 1 aimed to examine articles on Social Stories to determine the strengths and weaknesses of research that explored the use of this intervention for individuals with ASD. After searching and applying the inclusion criteria, 11 articles were selected. It was observed, after analysis, that the applications have taken place in several environments, suggesting that its field of action is expanding, although social stories are not commonly used and researched in Brazil. Study 2 analyzed the effectiveness of an intervention that promotes the learning of behaviors compatible with the inclusion of social skills in the repertoire of children with ASD, applied by their mothers after online training, presenting only the appropriate behavior and observing if there is a decrease in inappropriate behavior, based on previous studies and using the AB design. The participants were three mothers and three children between 2 and 4 years old diagnosed with ASD, who presented inappropriate behaviors in the face of a social demand. Each child had their own social story, indicating the desired repertoire. The behaviors worked by the mothers were maintained after one month, demonstrated by the answers in the social validation questionnaire answered by the participating mothers, pointing out the effectiveness of social stories as demonstrated in the literature.